BIODEGRADASI LIMBAH TANDAN KOSONG KELAPA SAWIT (Elaeis guineensis Jacq.) MENGGUNAKAN KONSORSIUM AKTERI PENGHASIL ENZIM SELULASE - Ina Darliana (Fakultas Kehutanan Universitas Winaya Mukti, 2020)
This research was conducted to observe the consortium cellulose enzyme activity that bacterial comes from oil palm empty fruit bunch waste. The use of bacterial isolates derived from oil palm empty fruit bunch waste is expected to have a good effect, because the bacteria have been adapted to live in a waste environment that has a high concentration of organic matter. The purpose of this study was to determine the activity of cellulose enzyme consortium of bacteria from palm oil waste in the process of biodegradation of oil palm empty fruit bunch waste (Elaeis guineensis Jacq.). The method used is descriptive method. The oil palm empty fruit bunch substrate was fermented and then cellulose enzyme activity was tested using the Somogyi-Nelson method. Doses of bacterial inoculums used in this study were 5% and 10%. The results showed that the consortium of bacteria from oil palm empty fruit bunch waste at a concentration of 5% with a value of 4.58 units / ml on day 21 had the highest cellulose enzyme activity.